ANALYSIS SIMPLE PAST TENSE ON CHARLOTTE’S WEB NOVEL - Widya Mega Syamdhani; Siska Rizkiani (PROJECT (Professional Journal of English Education), 2021)
Charlotte's Web novel is a novel by Elwyn Brooks White, the author of a famous Stuart Little novel. It was first published in Canada in 1952 by Fitzhenry & Whiteside Limited, Toronto. The purpose of this paper is to determine the use of simple past tense contained in the Charlottes’s Web novel. The data was taken from chapter 1 to 5 because these chapters are the orientation part of the story that introduces the characters in the story. Descriptive quantitave methods was applied since the results ofthis study are numbers and percentage which is explained in detail. It was found that there are 237 sentences of simple past tense existed in the chapters, consisting of 165 simple past tense verbal, 52 simple past tense nominal and 20 simple past tense verbal mix nominal. In other words, this chapters mainly discussed the story verbally. Keywords:  Grammar, Novel, Simple Past Tense